#TITLE_ALTERNATIVE# - Suwastika (NIM: 101 03 034), Erma
Abstarct: Module over a ring is a generalization of a vector space over a field. Field itself is a commutative division ring. One of the properties of vector space is the bases existence. Besides the vector space over a field, there is a module over a ring which has bases. Module over a ring which has a basis is called a free module. Projective module is more general than free module. Not all modules have projective cover, but every module has injective hulls. Hence, in this final project, the existence of injective hulls is showed, or in another word, every module has injective hulls.